Nta'tugwaqanminen : notre histoire : l'évolution des Mi'gmaqs de Gespe'gewa'gi - Malaborza, Sonya; Hebert, Marie-Claude (Canadian studies (Ottawa, Ontario), 2018)
Nta'tugwaqanminen speaks of the Gespe'gewa'gi Mi'gmaq vision, history, relation to the land, past and present occupation of the territory, as well as their place names and what they reveal in terms of ancient territorial occupation. It speaks of the treaties they agreed to with the British Crown, the respect of these treaties on the part of the Mi'gmaq people and the breach of these by various levels of governments. It explores the dispossession the Mi'gmaq of Gespe'gewa'gi (Northern New Brunswick and the Gaspe Peninsula) endured while the European settlers illegally occupied and developed the Gaspe Peninsula to their own advantage and the rights and titles the Mi'gmaq people still have on their lands. Nta'tugwaqanminen provides evidence that the Mi'gmaq of the Gespe'gewa'gi have occupied their territory since time immemorial, were its sole occupants prior to European settlement, and occupied it on a continuous basis. There are two voices in the book: that of the Mi'gmaq of the Gespe'gewa'gi, including the Elders, as they act as narrators of the collective history, and that of the researchers, who studied this history, including advanced investigation on place names as indicators of migration patterns.